A regional simulation and optimisation of renewable energy supply from wind and photovoltaics with respect to three key energy-political objectives - Sven Killinger; Kai Mainzer; Russell McKenna; Niklas Kreifels; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2014)
Currently, most photovoltaic (PV) modules are aligned in a way that maximizes the overall annual yields, which leads to significant peaks in electricity production and could threaten energy policy objectives such as security of supply as well as environmental sustainability. The exploitation of remaining PV potentials at seemingly economically sub-optimal inclinations and azimuth angles could partly counteract this trend by achieving significant temporal shifts in the electricity production. This paper addresses the potential of these counter-measures by evaluating the optimal mix of wind and PV installations with different inclination and azimuth angles in a regional context. It does so by adhering to three distinctive energy policy goals: economic efficiency, sustainability and security of supply. It is further assumed that the examined regions aim for energetic autarky. The hourly yields of wind parks and PV installations with different mounting configurations are simulated for four representative NUTS3-regions in Germany, based on assumed installed capacities and specific weather conditions. These profiles are combined with standardized regional electricity demand profiles and fed into an optimization model, which is employed to maximise each of the three energy policy goals independently. As a result the optimal installed capacity for PV for every possible configuration – determined by inclination and azimuth angles – and the optimal installed capacity of wind power are determined. The results indicate that the optimal mix differs significantly for each of the chosen goals and depends on regional conditions, but shows a high transferability in terms of general conclusions. For economic efficiency – the first of the three goals – a focus on a high share of wind power and south-oriented PV-systems is feasible for all German regions. When sustainability is chosen as the energy policy goal, results depend largely on the conventional power plant utilization and its CO2-equivalent emissions leading to a high share of PV-systems in ratio to wind power. When maximizing the third goal, the security of supply, PV plants facing east and west as well as wind turbines are preferred, since this homogenizes the daily combined PV production. The developed methodology is found to be robust with regard to the relative conclusions, whilst the absolute magnitude of the results is sensitive to the input data. Further work should focus on refining the representativeness of the four model regions and on quantifying the three considered criteria more holistically.
urn:nbn:de:swb:90-417553
Keywords: 330